2018
DOI: 10.7150/jca.24179
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of CCNE1 Amplification and Overexpression in Cancer Patients: A Systematic Review and Meta-analysis

Abstract: A number of studies revealed that CCNE1 copy number amplification and overexpression (on mRNA or protein expression level) were associated with prognosis of diverse cancers, however, the results were inconsistent among studies. So we conducted this systematic review and meta-analysis to investigate the prognostic values of CCNE1 amplification and overexpression in cancer patients. PubMed, Cochrane library, Embase, CNKI and WanFang database (last update by February 15, 2018) were searched for literatures. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…It is well-demonstrated that the dysregulation of CCNE1-CDK2 activity is implicated in multiple cancers, including bladder cancer, nasopharyngeal cancer and breast cancer [4244]. It has also been demonstrated that overexpression of CCNE1 was related to poor prognosis in diverse of cancers [45]. Shaye and colleagues found that overexpression of CCNE1 is an early event in the progression of breast cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-demonstrated that the dysregulation of CCNE1-CDK2 activity is implicated in multiple cancers, including bladder cancer, nasopharyngeal cancer and breast cancer [4244]. It has also been demonstrated that overexpression of CCNE1 was related to poor prognosis in diverse of cancers [45]. Shaye and colleagues found that overexpression of CCNE1 is an early event in the progression of breast cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…The complex of cyclin-dependent kinase 2 (CDK-2) and cyclin E is essential to drive G1/S transition (Malumbres & Barbacid, 2009). Cyclin E1overexpression seems to be associated with poor survival of cancer patients (Zhao et al 2018). A study in prostate cancer cells suggested that downregulation of cyclin E1 suppresses proliferation and induces G1/S arrest (Zhang et al 2019), which is in line with our results.…”
Section: Wb-ems-conditioned Serum From Colorectal Cancer Patients Attsupporting
confidence: 89%
“…Amplification of CCNE1 is associated with many cancer progressions including gastric cancer, bladder cancer, ovarian cancer and triple negative breast cancer and linked to poor prognosis. [40][41][42][43] In this study, we found that CCNE1 is up-regulated in cervical cancer cells. Functional studies showed that CCNE1 play critical roles in cervical cancer cell growth and cell cycle transition from G1to S phase.…”
Section: Discussionsupporting
confidence: 51%